Financial soundness index for the private corporate sector in Colombia - Juan S. Lemus-Esquivel; Carlos A. Quicazan-Moreno; Joge L. Hurtado-Guarin; Angelica Lizardo-Cuellar (Graduate Institute of International and Development Studies, 2015)
This paper evaluates the importance of building a composite metric of financial soundness for the private corporate sector in Colombia. Instead of relying on the individual and sometimes restrictive financial ratio analysis approach, the purpose of this document is to provide a single metric aimed at measuring the financial health of firms. Said metric, the financial soundness index, is derived by employing the cross-section approach of principal component analysis. For the time period of 2000-2013, the results allow to identify which industries have a weak, strong or similar balance sheet performance relative to that observed for the private corporate sector as a whole. Furthermore, validation tests on the index confirm the apparent relationship between accounting data of private firms that are debtors of the Colombian financial system and the credit risk perception of and materialization for financial intermediaries.
Keywords: L25; G30; G32; C3; 330; firms' financial soundness; principal component analysis; financial ratios; composite indices; financial stability